Combination of Intravenous Ascorbic Acid Administration and Hypothermia After Resuscitation Improves Myocardial Function and Survival in a Ventricular Fibrillation Cardiac Arrest Model in the Rat. (March 2014) - Tsai, Min‐Shan; Huang, Chien‐Hua; Tsai, Chia‐Ying; Chen, Huei‐Wen; Cheng, Hsaio‐Ju; Hsu, Chiung‐Yuan; Chang, Wei‐Tien; Chen, Wen‐Jone; Sinert, Richard
Abstract Objectives Intravenous (IV) administration of ascorbic acid during cardiopulmonary resuscitation (CPR) was reported to facilitate defibrillation and improves survival in ventricular fibrillation (VF) cardiac arrest. We investigated whether IV administration of ascorbic acid after return of spontaneous circulation (ROSC) can improve outcomes in VF cardiac arrest in a rat model and its interaction with therapeutic hypothermia. Methods Ventricular fibrillation–induced cardiac arrest followed by CPR and defibrillation was performed in male Wistar rats. After ROSC, the animals were equally randomized to the normothermia (NormoT), hypothermia (HypoT), ascorbic acid (AA+NormoT), and ascorbic acid plus hypothermia (AA+HypoT) groups. The AA+NormoT and AA+HypoT groups received IV ascorbic acid (100 mg/kg). In the HypoT and AA+HypoT groups, therapeutic hypothermia was maintained at 32°C for 2 hours. Results There were 12 rats in each group. Within 4 hours after ROSC, the HypoT, AA+NormoT, and AA+HypoT groups had significantly lower myocardial lipid peroxidation than the NormoT group. Within 4 hours following ROSC, the AA+NormoT group had a significantly better systolic function (dp/dt40) than the NormoT group (6887.9 mm Hg/sec, SD ± 1049.7 mm Hg/sec vs. 5953.6 mm Hg/sec, SD ± 1161.9 mm Hg/sec; p < 0.05). The AA+HypoT group also showed a significantly better diastolic function (–dp/dtmax) than the HypoT group (dp/dt40: 8524.8, SD ± 1166.7 mm Hg/sec vs. 7399.8 mm Hg/sec, SD ± 1114.5 mmHg/sec; dp/dtmax: –8183.4 mm Hg/sec, SD ± 1359.0 mm Hg/sec vs. –6573.7 mm Hg/sec, SD ± 1110.9 mm Hg/sec; p < 0.05) at the fourth hour following ROSC. Also at 4 hours, there was less myocytolysis in the HypoT, AA+NormoT, and AA+HypoT groups than the NormoT group. The HypoT, AA+NormoT, and AA+HypoT groups had significantly better survival rates and neurologic outcomes than the NormoT group. Compared with only five surviving animals in the NormoT group, there were nine, eight, and 10 in the HypoT, AA+NormoT, and AA+HypoT groups, respectively, with good neurologic outcomes at 72 hours. Conclusions Intravenous ascorbic acid administration after ROSC in normothermia may mitigate myocardial damage and improve systolic function, survival rate, and neurologic outcomes in VF cardiac arrest of rat. Combination of ascorbic acid and hypothermia showed an additive effect in improving both systolic and diastolic functions after ROSC.